2004
DOI: 10.1111/j.1468-3148.2004.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Q‐Methodology to Involve People with Intellectual Disability in Evaluating Person‐Centred Planning

Abstract: Objectives Person-centred approaches do not easily lend themselves to standard methods of evaluation. This study develops a technique that will involve service users and their circle of support in making individual plans. Methodology Q-methodology is a phenomenological approach, which enables the researcher to co-construct the stories of many people. Two people with learning disabilities and seven members of their circle of support were identified to participate in the study. They attended a stakeholder meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…O'Brien, 2004;Reid & Green, 2002;Smull & Lakin, 2002). As a consequence, planning meetings are sometimes not attended by any family member, lawyer, or the consumer (Mansell & Beadle-Brown, 2004); frequently, there are no meetings with the people involved (Combes et al, 2004), and although needs are identified, plans are often not implemented because of a lack of support solutions (Robertson et al, 2007b). For example, Dumas, De La Garza, Seay, and Becker (2002) illustrated that frequently participants actually do not understand their own person-centered planning process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…O'Brien, 2004;Reid & Green, 2002;Smull & Lakin, 2002). As a consequence, planning meetings are sometimes not attended by any family member, lawyer, or the consumer (Mansell & Beadle-Brown, 2004); frequently, there are no meetings with the people involved (Combes et al, 2004), and although needs are identified, plans are often not implemented because of a lack of support solutions (Robertson et al, 2007b). For example, Dumas, De La Garza, Seay, and Becker (2002) illustrated that frequently participants actually do not understand their own person-centered planning process.…”
Section: Discussionmentioning
confidence: 98%
“…Person-centered planning covers a wide range of procedures and guidelines focused on the creation of fundamental changes in the lives of people with intellectual and developmental disabilities (Cloutier, Malloy, Hagner, & Cotton, 2006;Combes, Hardy, & Buchan, 2004;Holburn, 2002Holburn, a, 2002b. The purpose of person-centered planning is to develop collaborative, goal-oriented, and individualized programs that are focused on community presence, community participation, positive relationships, respect, and competence (Cloutier et al, 2006;Keyes & Owens-Johnson, 2003;J.…”
mentioning
confidence: 99%
“…Combes et al. 45 have shown it to be a feasible approach even among people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This small sample technique provides depth rather than generalizability and is particularly appropriate for sensitive topic research. 35,[39][40][41][42] Qmethodology has been extensively used in qualitative psychological research to understand human behavior, 39,[43][44][45][46] workplace behaviors, 41,47 among others. Therefore, in a relatively unexplored area like PWU, this technique can provide insights into the underlying dynamics of perceptions of the actors.…”
Section: Methodsmentioning
confidence: 99%